2020
DOI: 10.1038/s41467-019-14109-x
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus blocks host transcription termination via the bimodal activities of ICP27

Abstract: Infection by viruses, including herpes simplex virus-1 (HSV-1), and cellular stresses cause widespread disruption of transcription termination (DoTT) of RNA polymerase II (RNAPII) in host genes. However, the underlying mechanisms remain unclear. Here, we demonstrate that the HSV-1 immediate early protein ICP27 induces DoTT by directly binding to the essential mRNA 3' processing factor CPSF. It thereby induces the assembly of a dead-end 3' processing complex, blocking mRNA 3' cleavage. Remarkably, ICP27 also ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(112 citation statements)
references
References 64 publications
(88 reference statements)
11
95
0
Order By: Relevance
“…HSV-1-induced APA changes could be due to changes in PAS selection during transcription and/or selective loss of individual APA isoforms. To distinguish between these mechanistic models, we directly compared our PAS-seq data with nascent RNA sequencing (4sU-seq) data, which provides information on transcription activities [13]. Meta-analyses of 4sU-seq signals in mock or HSV-1infected cells along the genes that showed HSV-1-induced higher usage of upstream PAS (DtoP) revealed two interesting differences.…”
Section: The Relationship Between the Hsv-1-induced Apa Changes And Tmentioning
confidence: 99%
See 2 more Smart Citations
“…HSV-1-induced APA changes could be due to changes in PAS selection during transcription and/or selective loss of individual APA isoforms. To distinguish between these mechanistic models, we directly compared our PAS-seq data with nascent RNA sequencing (4sU-seq) data, which provides information on transcription activities [13]. Meta-analyses of 4sU-seq signals in mock or HSV-1infected cells along the genes that showed HSV-1-induced higher usage of upstream PAS (DtoP) revealed two interesting differences.…”
Section: The Relationship Between the Hsv-1-induced Apa Changes And Tmentioning
confidence: 99%
“…We have previously shown that ICP27, when bound to upstream GC-rich sequences, can activate PAS (Fig. 4G) [13]. To test if the GC contents of the different classes of intronic PAS impact ICP27 binding, we took advantage of the ICP27 CLIP-seq dataset that we generated previously [13].…”
Section: Mechanisms For Hsv-1-mediated Apa Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The HSV IE gene product ICP4 acts as a major transcriptional activator that is essential to regulate viral E and L genes. ICP27 promotes viral infection through splicing, processing, and mRNA export [ 17 ]. The present study explored CyHV-2 IE genes through high-throughput sequencing combined with the use of inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…HSV-1 ICP27 was recently shown to block the transcription termination of host genes by inhibiting mRNA 3′ processing. Furthermore, ICP27 can act as a sequence-dependent activator of mRNA 3′ processing to promote efficient transcription termination of viral transcripts, indicating that HSV-1 ICP27 plays an important role in host shutoff [27].…”
Section: Main Textmentioning
confidence: 99%